An Overview on the Potential Roles of EGCG in the Treatment of COVID-19 Infection - Bimonte S; Forte CA; Cuomo M; Esposito G; Cascella M; Cuomo A (Dove Medical Press, 2021)
Sabrina Bimonte,1,* Cira Antonietta Forte,1,* Massimiliano Cuomo,2 Gennaro Esposito,1 Marco Cascella,1 Arturo Cuomo1 1Division of Anesthesia and Pain Medicine, Istituto Nazionale Tumori - IRCCS - Fondazione G. Pascale, Naples, Italy; 2S.C. Project Management e Formazione, Istituto Nazionale Tumori - IRCCS - Fondazione G. Pascale, Naples, Italy*These authors contributed equally to this workCorrespondence: Sabrina BimonteDivision of Anesthesia and Pain Medicine, Istituto Nazionale dei Tumori, IRCCS Fondazione G. Pascale, Naples, ItalyEmail s.bimonte@istitutotumori.na.itAbstract: Coronavirus disease-19 (COVID-19) pandemic is currently ongoing worldwide and causes a lot of deaths in many countries. Although different vaccines for the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection have been developed and are now available, there are no effective antiviral drugs to treat the disease, except for Remdesivir authorized by the US FDA to counteract the emergency. Thus, it can be useful to find alternative therapies based on the employment of natural compounds, with antiviral features, to circumvent SARS-CoV-2 infection. Pre-clinical studies highlighted the antiviral activities of epigallocatechin-3-gallate (EGCG), a catechin primarily found in green tea, against various viruses, including SARS-CoV-2. In this review, we summarize this experimental evidence and highlight the potential use of EGCG as an alternative therapeutic choice for the treatment of SARS-CoV-2 infection.Keywords: COVID-19, EGCG, SARS-CoV-2, tea polyphenols, antiviral properties